THE HEADSCARF ISSUE AND ISLAMIC FEMINISM IN ORHAN PAMUK’S SNOW (International Conference on Social and Islamic Studies, 2021)
The paper titled “The Headscarf Issue and Islamic Feminism in Orhan Pamuk’s Snow” shall attempt to explore and interpret Orhan Pamuk as Turkey’s most renowned and controversial writer who boldly expresses his voice regarding the socio-political reality of Turkish history with special reference to the novel Snow as an intriguing representation of Islamic Feminism. In Snow, the way the ‘headscarf girls’ resists against the government’s banning of wearing headscarves without even taking their consent which result in suicides of young girls are instances of the oppression and restraints put upon women’s rights to choose their way of life within patriarchal and religious realms. The notion of art and theatre as symbols of women’s road to freedom also plays a significant role in the novel. Hence, Snow is a microcosm of Turkey, its society, its politics and its Ottoman culture, caught between the East-West dichotomies and people struggling to find sense of one’s identity and belongingness. By engaging such concerns, Orhan Pamuk deconstructs the binaries of gender and emphasizes upon the unifying position of both East and West as metaphorical means for positive development and equality of all genders and between nations. The paper attempts to negotiate the way Orhan Pamuk debunks the Western misconception of Islamic women as mere victims of patriarchal fundamentalism that denies emancipatory modes of Western feminism but rather as being rebellious by committing suicides or participating in art and theatre as the most liberating means of exercising their individual will fearlessly against the so-called power structures.